LAYANAN BIMBINGAN KARIER BERBANTUAN APLIKASI RENCANAMU.ID UNTUK MENINGKATKAN KEMATANGAN KARIER MENGHADAPI SELEKSI PERGURUAN TINGGI - Ridwan Ridwan; Heris Hendriana; Ardian Renata Manuardi (IKIP Siliwangi, 2022)
This study aims to implement the implementation of career guidance services, find out the responses of students, find out what obstacles are faced by students and find out the obstacles faced by Guidance and Counseling teachers in the implementation of career guidance services assisted by the rencanamu.id application to assist students in maturity. career. The method used is descriptive qualitative research. The results of the study can be concluded that the implementation of career guidance is carried out face-to-face and online with four (4) sessions. Positive student responses to the implementation of career guidance services assisted by the Paketmu.id application. The obstacles faced by students in implementing career guidance services assisted by the Planmu.id application in increasing career maturity are often feeling bored and bored, then the signal must be stable so that it is often delayed and consuming quota. The obstacle experienced by BK teachers is that they find it difficult to condition students considering learning situations that are carried out online and at different times and rhythms. Discipline and motivation of students in completing applications is a challenge for teachers given the different backgrounds and abilities of students. All obstacles are overcome by the success of the subject of students reaching the expected career maturityKeywords:Career Maturity, career guidance and application of rencanamu.id